Numerical Study of Thermal Comfort Evaluation in Naturally Ventilated Classrooms - Prasetyo, Bowo Yuli; Muliawan, Rizki; Afifah, Andini Luthfiyyah; Wang, Fujen (Bandung State Polytechnic (Politeknik Negeri Bandung), 2023)
The classroom is one of the important facilities in teaching and learning activities. Just like any other room, ensuring thermal comfort becomes a vital aspect for its occupants. This study aims to evaluate environmental conditions and the thermal comfort experienced by classroom occupants through numerical methods. The evaluation involves the integration of the Predicted Mean Vote (PMV) and Predicted Percentage of Dissatisfied (PPD) equations into Computational Fluid Dynamics (CFD) simulations using a user-defined function. Furthermore, extensive field measurements and questionnaire surveys are also employed to support the simulation process. The results indicate that the air temperature tends to be high, reaching 30.91°C. Meanwhile, the air velocity within the room, particularly in the occupied areas, is significantly low, with an average value of 0.04 m/s. According to the ASHRAE Standard 55, the classroom is perceived as uncomfortable, as evidenced by a PMV value of 1.38 and a PPD of 44.94%. Therefore, efforts are required to enhance the thermal comfort in the space.